Analysis of the Impact of Sleep Apnea on Cardiovascular Health and Mortality: A Long-Term Cohort Study - Riddhi Chawla; Abhishek Jahagirdar; Happy Riba; Tharini Satheesh; Pratiksha Somwanshi; Shiba Brata Behera; Sunil K. Gulia (Wolters Kluwer Medknow Publications, 2024)
Background: A common sleep problem linked to poor cardiovascular outcomes and death is "sleep apnea (SL)." Nevertheless, little is known about how SL affects cardiovascular health in the long run. The purpose of this research was to investigate the relationship between a tertiary care center's long-term cohort's cardiovascular morbidity and mortality and the severity of their SL. Methods: Between January 1, 2010, and December 31, 2020, 500 individuals at a tertiary care facility who had been diagnosed with SL participated in this retrospective cohort research. Electronic medical records were used to collect patient data, which were then examined for cardiovascular outcomes, treatment methods, comorbidities, sleep research findings, and demographics. Heart failure, myocardial infarction, stroke, and cardiovascular-related mortality were among the cardiovascular events that were noted throughout the follow-up period, and the severity of SL was classified using the "apnea-hypopnea index." Findings: Of the 500 patients in the cohort, 60% were men and the mean age was 55.7 years. Fifty percent of people had one or more cardiovascular risk factors, including diabetes, high blood pressure, and smoking. During the course of the follow-up, 100 cardiovascular-related fatalities were reported, and 40% of patients had at least one cardiovascular event. The severity of SL was shown to be positively correlated with the occurrence of cardiovascular events (16.7% in mild, 25% in moderate, and 40% in severe SL, P < 0.05). Conclusion: In a cohort of patients receiving tertiary care, this research shows a substantial correlation between the severity of SL and cardiovascular morbidity and death. It is crucial to identify and treat SL early on to reduce cardiovascular risks and enhance patient outcomes. To further understand the underlying processes and develop treatment approaches for people with cardiovascular comorbidities and SL, more research is necessary.